Analysis of the Use of Environmentally Friendly Raw Materials and Environmental Awareness on Purchasing Decisions and Consumer Loyalty in the Central Java Manufacturing Industry - Utami, Eva Yuniarti; Supriandi, Supriandi; Pahrijal, Rival (Westscience Press, 2024)
This research investigates the positive relationships between environmentally friendly raw materials, environmental awareness, purchasing decisions, and consumer loyalty within the Central Java manufacturing industry. Utilizing a quantitative approach, Structural Equation Modeling (SEM) with Partial Least Squares (PLS) analysis is employed to analyze data collected from 125 respondents. The findings reveal significant positive associations between the use of environmentally friendly raw materials and purchasing decisions, environmental awareness and purchasing decisions, environmental awareness, and consumer loyalty, as well as environmentally friendly raw materials and consumer loyalty. These results emphasize the importance of sustainability initiatives and environmental awareness in driving consumer behavior and fostering loyalty in the manufacturing industry.